2012
DOI: 10.1007/s10517-012-1854-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Cholestasis in HCV and HBV Infection

Abstract: Structural analysis of hepatocytes in liver biopsy specimens from patients with hepatitis C and C+B with intracellular cholestasis was carried out. Large foci of bile components in hepatocytes led to cell damage, eventuating in cell destruction and death. The cholestatic variant of mixed infection was characterized by destructive necrotic changes in hepatocytes and progressive fibrosis of the liver. Destruction of the hepatocyte cytoplasmic organelles was associated with high activity of the infectious process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Apart from the suspected mediators and their origin, the onset of pruritus is closely associated with the development of intrahepatic cholestasis[ 31 ]. Although hepatic disorders such as chronic infection with viral hepatitis, primary biliary cirrhosis or primary sclerosing cholangitis are considered the main cause of intrahepatic cholestasis[ 32 , 33 ], the elevation of bile salts and μ-opioids levels in patients with intrahepatic cholestasis is largely associated with pruritus[ 34 ]. To date, the causative link between bile salts levels and severity of pruritus has not yet been investigated.…”
Section: Mechanisms Of Hcv Infection and Treatment- Associated Pruritmentioning
confidence: 99%
“…Apart from the suspected mediators and their origin, the onset of pruritus is closely associated with the development of intrahepatic cholestasis[ 31 ]. Although hepatic disorders such as chronic infection with viral hepatitis, primary biliary cirrhosis or primary sclerosing cholangitis are considered the main cause of intrahepatic cholestasis[ 32 , 33 ], the elevation of bile salts and μ-opioids levels in patients with intrahepatic cholestasis is largely associated with pruritus[ 34 ]. To date, the causative link between bile salts levels and severity of pruritus has not yet been investigated.…”
Section: Mechanisms Of Hcv Infection and Treatment- Associated Pruritmentioning
confidence: 99%
“…On the basis of immune interactions between virus and host, HBV infection can have diverse clinical manifestations, including acute hepatitis, chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma 7 . However, cholestatic hepatitis due to HBV infection were reported very rarely in literature 5 . Our patient represents a typical case of acute HBV infection acquired at the age of 56 years and expected to resolve spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence of hepatitis; jaundice and occasionally acute liver failure develops in rest one third of patients with acute HBV infection 7 . Cholestatic hepatitis is one of very rare manifestations of acute HBV infection, but when develop it leads to prolonged hospital stay and increased medical expenses 5 . Rapid improvement of the clinical symptoms and signs have been reported in patients with cholestatic hepatitis A (HAV) after use of corticosteroid 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Cholestasis is a common risk factor that is complicated in enterohepatic diseases, especially in liver diseases including fibrosis, cirrhosis, and hepatitis. [1][2][3] Clinical studies revealed that cholestasis is negatively associated with hepatitis outcomes in chronic hepatitis B virus infection, and intrahepatic cholestasis of pregnancy (ICP) patients were more susceptible to Hepatitis B Virus (HBV) infection. 4 Notably, bile acids are overall accumulated in patients with hepatitis virus infection, 5 and mice infected with HBV showed an apparent enhancement of cholesterol 7α-hydroxylase (CYP7A1), the rate-limiting enzyme promoting the bile acids de novo synthesis.…”
Section: Introductionmentioning
confidence: 99%